(untitled) (El Hilo de la Fabula, 2020)
The translation of Italian poetry was very important throughout the 20th century, especially by some authorial names that left their mark and opened a dialogue with other cultures. It is possible to remember Giuseppe Ungaretti, Euge- nio Montale, Umberto Saba and also Andrea Zanzotto and Giorgio Caproni. The first decade of the new millennium saw the circulation of a series of poetic anthologies and new volumes of poetry. In this essay, we propose a nuanced re- ading of Snow Easter by Enrico Testa, from the standing point of the 2016 Brazilian edition.